PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA CAMILAN KULPIKERS DI KAMPUNG BALI JAKARTA PUSAT - Erika Tiana Sari; Erlita Kurniawaty (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the price and quality of the product on purchasing decisions at Kulpikers Snacks, Central Jakarta. The method used in this study is a quantitative method. The population in this study was 5,819 consumers, the sampling method used was the slovin technique totaling 98 consumers, using the accidental sampling technique. Data collection techniques through primary and secondary data. The analysis used regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of this study are product quality (X1) and price (X2) have a positive and significant effect on purchasing decisions (Y) with the regression equation Y = 6.478 + 0.188 X1 + 0.603 X2 + α. The determination coefficient has a simultaneous effect of 55.9%. Partial hypothesis testing obtained the results of product quality (X1) of t count> t table or (7.973> 1.984), then Ho1 is rejected and Ha1 is accepted. This means that there is a positive and significant influence between the independent variables, namely Product Quality (X1) on purchasing decisions (Y).  Partial hypothesis test obtained the result of price (X2) of t count> t table or (10.705> 1.984). then Ho2 is rejected and Ha2 is accepted. This means that there is a positive and significant influence between the independent variable, namely price (X2) on purchasing decisions (Y). Simultaneous hypothesis test between product quality variables (X1) and price (X2) obtained the result of F count> F table or (60.300> 1.984). Thus Ho3 is rejected and Ha3 is accepted, meaning that there is a significant influence simultaneously between product quality (X1) and price (X2) on purchasing decisions (Y) at Kulpikers Snacks, Central Jakarta.